Experimental Archaeology at L'Esquerda - Crops, Storage, Metalcraft and Earthworks in Mediaeval and Ancient Times - Ollich, Imma; Rocafiguera, Montserrat de; Ocaña, Maria; Cubero, Carme; Amblàs, Oriol (IntechOpen, 2012)
None